Pengembangan Aplikasi Mobile untuk Penyediaan Informasi Sekitar Kampus Binus Berbasis Web - Yosanny, Agustinna; Halim, Adriani (Bina Nusantara University, 2013)
Sometimes we find difficulties in obtaining the necessary information as limited to place and time, as well as the media used. One example is limitations in obtaining the necessary information about facilities available at the nearby of Binus University campus. Based on this case, we propose information media providing facilities around Binus University campus that can be accessed anytime and anywhere using mobile web technology guided by Google maps. The features of Google maps can also help users locate the facility. The methodology used in this research is analysis and design. Results that can be obtained from this research is a mobile-web application that provides complete information about the environment around BINUS campus that can be accessed by students and the surrounding community. Using this application, BINUS students can obtain the necessary information about the campus environment easily and quickly.